Evaluation of the anterior loop of the mental nerve incidence and extension in different age groups in Sulaimania city using digital panoramic imaging system - Lamia H Al-Nakib; Sarkawt K Rasul (College of Dentistry/ University of Baghdad, 2014)
Background: The anterior loop of mental nerve is commonly described as that part of the neurovascular bundle that transverses anterior and inferior to the mental foramen only to loop back to exit the mental foramen. The aim of the study is to evaluate the incidence and extension of anterior loop of mental nerve by using digital panoramic imaging system to avoid nerve damage during different surgical procedures in dentistry. Materials and Method: Panoramic image was taken for all 400 patients and stored in the computer. Then Horizontal and Vertical for the anterior loop extension when exist was measured and recorded in a special case sheet prepared for each subject. Results: Results indicated that out of 400 patients there were only 25 patients (6.25%) having anterior of the inferior alveolar nerve, 14 cases (56%) of them were males and 11 cases (44%) were females. The extension of the anterior loop of mental nerve was with wide range, for horizontal extension it was 1.3-6.36mm with significant difference between right and left sides, and with vertical extension was between 1.44 -5.98mm with no significant difference between the right and left sides. Conclusion: No significant difference among subjects according to sex and the pattern of visualization of the anterior loop was shown. The anterior loop was visible in 6.25% of the dental panoramic radiographs with 3.5% for males and 2.75% for females